Daemons of the shadow realm. 5 - Arakawa, Hiromu, 1973- (Deamons of the shadow realm, 2024)
After a fierce scuffle against Long-Arm and Long-Leg, Yuru meets their timid master, Ken--who happens to be Dera's half brother! Ken reveals that his father had helped Yuru's parents go into hiding, prompting Dera to contact a shady shaman for more intel on the previous Tadera clan head. Meanwhile, another tragedy is about to befall Higashi Village, courtesy of a swordsman named Ivan Yosano...